The effect of the challenges experienced by nurses during the pandemic on their intention to leave work: the mediating role of the performance - Tuğba Öztürk Yıldırım; Hilal Kuşcu Karatepe (BMC Nursing)
Abstract Background During the COVID-19 pandemic, negative working conditions in the nursing profession have worsened, and nurses have experienced various challenges that have increased their intention to leave work. Findings on the role of nurse performance under such conditions are limited. Aims This study aimed to investigate the role of performance in the effect of the challenges experienced by nurses during the pandemic on their intention to leave work. Methods This descriptive and cross-sectional study was conducted between July 2022 and August 2023 in Turkey using an online survey. A total of 462 nurses participated in the study, which employed the non-probability random and snowball sampling methods. Results The mediating factors in the effect of the challenges experienced by nurses during the pandemic on their intention to leave work were task performance (β = 0.07), contextual performance (β = 0.05), and counterproductive work behavior (β = 0.12), respectively. Conclusions This study determined that task performance, contextual performance, and counterproductive work behavior played an important role in the effect of the challenges experienced by nurses during the pandemic on their intention to leave work. The present results may serve as a guide in determining effective strategies to be employed in possible pandemic situations.